Consumption Of Transfer Factor Belle Vie On The WUS With Menstrual Disorders In The City Of Makassar - Kesna Nathasya Novitasari; Andi Nurlinda; Reza aril ahri (Window of Health, 2018)
Reproductive age women having lots of menstrual problems or abnormal menstruation, such as menstrual syndrome and irregular menstruation. This research aims to review and analyze in-depth information regarding the effectiveness of the consumption of the Transfer Factor Belle Vie Against menstrual disorders in women age early.